The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.4187/respcare.01236
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Single Ventilator to Support 4 Patients: Laboratory Evaluation of a Limited Concept

Abstract: INTRODUCTION:A mass-casualty respiratory failure event where patients exceed available ventilators has spurred several proposed solutions. One proposal is use of a single ventilator to support 4 patients. METHODS: A ventilator was modified to allow attachment of 4 circuits. Each circuit was connected to one chamber of 2 dual-chambered, test lungs. The ventilator was set at a tidal volume (V T ) of 2.0 L, respiratory frequency of 10 breaths/min, and PEEP of 5 cm H 2 O. Tests were repeated with pressure targeted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
80
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 15 publications
1
80
0
5
Order By: Relevance
“…The addition of high-efficiency particulate air (HEPA) filters to the expiratory limb of the circuit can help minimize aerosolization if the ventilator does not have a closed circuit. Other creative approaches include splitting a ventilator to support several patients simultaneously by using T-tubes and pressure-cycled ventilation [6][7][8].…”
Section: Treatmentmentioning
confidence: 99%
“…The addition of high-efficiency particulate air (HEPA) filters to the expiratory limb of the circuit can help minimize aerosolization if the ventilator does not have a closed circuit. Other creative approaches include splitting a ventilator to support several patients simultaneously by using T-tubes and pressure-cycled ventilation [6][7][8].…”
Section: Treatmentmentioning
confidence: 99%
“…They observed wide variability in measured tidal volume (Vt) and end-expiratory lung volume, so they concluded that the technique should be avoided because of potential danger. 3 Accordingly, the authors argued that the stockpiling of ventilators should be the firstline solution when massive emergencies are forecast; only after their depletion, strategies such as the 'double circuit' should be implemented for the shortest possible duration. 4 5 On 20 February 2020, the first case of COVID-19 emerged in the Lombardy region, northern Italy.…”
mentioning
confidence: 99%
“…[24][25][26][27][28] The concept of sharing a single ventilator for multiple patients has also been proposed as a solution to increase ventilator capacity during this coronavirus crisis. [30][31] A device for sharing a ventilator in this fashion has recently received emergency approval from the Food and Drug Administration in the United States. 32…”
Section: Consider the Challenges In Critical Care Staffing And Suppliesmentioning
confidence: 99%